RESEARCH ON FACTORS INFLUENCING THE TRANSFORMATION OF THE VALUE SYSTEM IN YOUNG STUDENTS - Jabbarov, Rashid; Mustafayev, Mushvig (Health and Society, 2025)
The article analyzes values ​​as a contradictory and ambiguous concept. Various and alternative concepts devoted to this problem are classified, and approaches to the study of values ​​in modern psychology are grouped according to various criteria. At the same time, the article notes that the existing approaches to values ​​indicate that the value system has a different structure, and each of them has its own place in psychological research. In conclusion, it is noted that although there are different views among authors regarding the concept of values ​​and its content, most researchers believe that values ​​play an important role in the structure of personality and the regulation of its behavior. Experimental research shows that with age, the process of transformation of values ​​takes shape in a specific direction. If in earlier age periods the reasons for evaluating moral actions were conditioned by various factors, in later age periods students associated the idea of ​​​​the wrongness of these or other moral actions with specific reasons. The results of the study showed that while friendship and justice were more important for boys than for girls, girls gave more preference to values ​​​​such as money and fame. The obtained result shows that the correct assessment of values ​​depends on the students’ worldview, intellectual level and sphere of knowledge.